LEIDYBOS TYRIMŲ KONFERENCIJA FLORENCIJOJE - MACEVIČIŪTĖ, ELENA (Knygotyra, 2014)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, LT-01513, Vilnius, Lietuva El. paštas: elena.maceviciute@gmail.com